Isolation of Saprolegnia aenigmatica oomycetes and protocol for experimental infection of pacu (Piaractus mesopotamicus) (Acta Scientiarum. Biological Sciences, 2018)
Successful disease treatment depends on molecular studies under indoor conditions with experimental infection protocols that facilitate understanding the disease and the drug`s efficacy. The internal transcribed spacer (ITS) region was sequenced from three isolates, which were identified as Saprolegnia aenigmatica. Subsequently, healthy fish were immunosuppressed with dexamethasone (1.2 mg kg-1) and descaled to the skin using a sharp scalpel. These individuals were isolated in individual aquariums maintained at 22°C. Individuals in one group were subcutaneously inoculated with 9,000 zoospores (DDZ treatment), a second group was exposed to oomycetes in water with three colonized baits (DDB), a third group was maintained in water without zoospores (DD), and a control group (C) consisted of healthy animals. After 48 and 96 hours, two animals from each group were euthanized for fungal re-isolation. The fish from groups DD and C did not show clinical signs, and no oomycetes were isolated. The animals from the DDZ and DDB groups showed cotton-wool-like masses on the skin, and S. aenigmatica was re-isolated. Thus, for infection using zoospores or baits parasitized by S. aenigmatica, an immunosuppressor (dexamethasone) and a sharp scalpel can be used effectively to establish an experimental infection in P. mesopotamicus.